Filament Formation in TaOx Thin Films for Memristor Device Application: Modeling Electron Energy Loss Spectra and Electron Transport. (20th October 2022) - Jiang, Jie; Pachter, Ruth; Mahalingam, Krishnamurthy; Ciston, Jim; Dhall, Rohan; Bondi, Robert J.; Marinella, Matthew J.; Telesca, Donald A.; Ganguli, Sabyasachi
Abstract: Although understanding filament formation in oxide‐based memristive devices by theory has emerged, there are still fundamental unanswered questions. Importantly, for practical application of thin films the material in its amorphous state is to be considered, but mostly lacking so far, and details on sub‐stoichiometry are also scarce. To gain insight into the optical and electronic properties of sub‐stoichiometric amorphous tantalum oxide (TaO x ), the electron energy loss spectrum (EELS) of model systems is characterized theoretically and electron transport characteristics are analyzed in detail. Calculated blue‐shifts by increasing sub‐stoichiometry explained the measurements, potentially suggesting estimation of oxygen vacancy concentrations through EEL spectra. Electron transport results based on TaO x material models validated by EELS measurements show that oxygen vacancy filamentary paths are initiated at low bias upon increasing sub‐stoichiometry yet noting an interplay with the local amorphous structure. Contact resistances at interfaces of the TaO x switching layer and a tantalum scavenging layer or titanium nitride electrode are quantified, indicating the possibility for either oxygen vacancy‐ or metal cluster‐based conduction mechanisms at the interface. The computational work, combined with experimental characterization for validation, provides a basis for investigating effects of sub‐stoichiometry on filament formation in TaO x thin film memristive devices. Abstract : To explain filament formation in sub‐stoichiometric tantalum oxide (TaO x ) thin film memristive devices, theoretical characterization of electron energy loss spectra (EELS) is validated by measurements. Predicted EELS blue‐shifts when increasing sub‐stoichiometry estimate the oxygen vacancy concentration. Electron transport calculations for amorphous TaO x and metal–TaO x –metal stacks of varying sub‐stoichiometry elucidate oxygen vacancy assisted transmission paths of the conduction filaments.